Interactive Effects of CO2, Temperature, Irradiance, and Nutrient Limitation on the Growth and Physiology of the Marine Diatom Thalassiosira pseudonana (Coscinodiscophyceae). Issue 6 (10th August 2020) - Laws, Edward A.; McClellan, S. Alex; Passow, Uta
Abstract : The marine diatom Thalassiosira pseudonana was grown in continuous culture systems to study the interactive effects of temperature, irradiance, nutrient limitation, and the partial pressure of CO2 (pCO2 ) on its growth and physiological characteristics. The cells were able to grow at all combinations of low and high irradiance (50 and 300 μmol photons · m −2  · s −1, respectively, of visible light), low and high pCO2 (400 and 1, 000 μatm, respectively), nutrient limitation (nitrate‐limited and nutrient‐replete conditions), and temperatures of 10–32°C. Under nutrient‐replete conditions, there was no adverse effect of high pCO2 on growth rates at temperatures of 10–25°C. The response of the cells to high pCO2 was similar at low and high irradiance. At supraoptimal temperatures of 30°C or higher, high pCO2 depressed growth rates at both low and high irradiance. Under nitrate‐limited conditions, cells were grown at 38 ± 2.4% of their nutrient‐saturated rates at the same temperature, irradiance, and pCO2 . Dark respiration rates consistently removed a higher percentage of production under nitrate‐limited versus nutrient‐replete conditions. The percentages of production lost to dark respiration were positively correlated with temperature under nitrate‐limited conditions, but there was no analogous correlation under nutrient‐replete conditions. The results suggest that warmer temperatures and associated more intense thermal stratification of ocean surface waters could lower net photosynthetic rates if the stratification leads to a reduction in the relative growth rates of marine phytoplankton, and at truly supraoptimal temperatures there would likely be a synergistic interaction between the stresses from temperature and high pCO2 (lower pH).